Preserving cultural Malay traditional jewellery: new design of Kerongsang Tok - Shamsuddin, Rozita; Abdull Manan, Emilia; Abdull Manan, Mohd Masdi; Mohd Sharif, Mohd Hakim; Muda, Muhammad Shafiq; Wan Sulaiman, Wan Salwana (Universiti Teknologi MARA, Kedah, 2023)
Kerongsang Tok is an old Malay Traditional Jewellery made of gold metal or gold plated and consists of 3 forms of shirt buttons or better known as kerongsang which are matched with baju kebaya labuh or kebaya pendek which has been famous among the Malays, Portuguese, Nyonya Peranakan and the Ceti in Melaka for centuries. Since Kerongsang Tok is no longer as popular as it once was, this study proposed a new inspiration for the design of Kerongsang Tok for the benefit of future generations. This research is to renew the design that might sparkthe interest in preserving and promoting traditional Malay cultural heritage, which has led toa resurgence of interest in Kerongsang Tok. The main objectives of this study are to developa new inspiration for the Kerongsang Tok design and to preserve the Malay heritage through the new creation of the Kerongsang Tok. This design research is basedon the ideationprocess that is related directly to the basics of Kerongsang Tok design. The ideation begins with the development of the Kerongsang Tok design by using Malay motifs to enhance the new inspiration of the Kerongsang Tok design. A survey has been carried out to choose the best design based on the opinion of jewellery designers, goldsmiths, academicians, andstudents in jewellery field. The new inspiration for Kerongsang Tok design has been produced based on the result of the survey. This research will contribute to preservingMalaysia's heritage and become a reference for future generations and initiate appreciation towards our cultural heritage.